Oral hairy leukoplakia: An exfoliative cytology study - Ajay Reginald; B Sivapathasundharam (Wolters Kluwer Medknow Publications, 2010)
Oral hairy leukoplakia (OHL) is a white, hyperplastic, vertically corrugated lesion that occurs on the lateral border of the tongue, usually unilateral. Caused by the Epstein-Barr Virus (EBV), the lesion is said to be an early indicator of an immune deficiency status, thereby unmasking subclinical systemic conditions. OHL mimics many other white lesions of the oral cavity; therefore, it becomes imperative to identify the lesion. This study used exfoliative cytology, a noninvasive procedure, which helped in identifying the cellular changes brought about by the virus in the oral epithelium. The study revealed a subclinical phase of OHL, where the cellular changes were seen even before the appearance of the clinical lesion.